Efficacy of 10-day Sequential Treatment for Helicobacter pylori Eradication - Naz, Lubna; Waqar, Ayesha; Mahboob, Maryam; Bhatti, Asif Raza; Iftikhar, Fazeelat; Rafique, Zahra (Pakistan Armed Forces Medical Journal, 2024)
Objective: To assess the effectiveness and tolerability of a ten-day sequential regimen for the eradication of Helicobacter pylori.Study Design: Quasi-experimental study.Place and Duration of Study: Department of Medicine, NESCOM Hospital, Islamabad Medical Complex, Pakistan from Aug 2021 to Aug 2022.Methodology: The patients were divided into two groups. The sequential therapy group (Group-A) was administered dual therapy including a proton pump inhibitor (Lansoprazole 30mg) plus Amoxicillin 1 gram given twice daily for first five days, followed by a triple therapy including Lansoprazole 30mg, Levofloxacin 500 mg and Tinidazole 500mg, all twice daily for remaining five days. Whereas traditional therapy group (Group-B) was given Lansoprazole 30 mg, Clarithromycin 500 mg, and Amoxicillin 1000 mg twice daily for total 14 days.Results: A total of 200 Helicobacter pylori positive cases were included. The mean age of all patients was 36.60±12.49 years whereas mean Body Mass Index was 28.19±4.02. A total of 140 patients had successful treatment in both groups out of which 87(87%) were in sequential treatment group and 53(53%) in the traditional treatment group (p-value